Dental Calculus as A Source of Bacterial Dna Analysis in Prehistoric Humans: a Systematic Literature Reviews - Fitri Handayani; Murnisari Darjan; Yuti Malinda; Lutfi Yondri (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Dental calculus is defined as mineralized dental plaque that is formed through the complex interaction between saliva and bacteria which adhere to the surface of the teeth. The plaque contains sources of bacterial genetic material which has the potential to be a source of information on ancient human health. Genetic sequences in the form of DNA are generated through a series of DNA extraction and through preparation of calculus samples of prehistoric human teeth. This research was conducted to determine the result of the identification of bacterial DNA found from ancient human skeletal dental calculus. This research was conducted using a literature study method through a systematic approach by collecting articles through an electronic search engine that fits the inclusion and exclusion categories. Of the 8 articles that met the criteria, 6 were research articles and 2 were reviewed articles. Four articles examined disease in ancient humans from the extraction of dental calculus in the paleolithic to early neolithic periods, two articles examined samples comparing modern humans and prehistoric humans and two others were reviewed article. Research that uses analysis of dental calculus has the potential to produce some information on life in pre-historic times besides that this research is also beneficial in future research so that it can be said that DNA analysis research uses dental calculus as a time capsule, because in dental calculus store a lot of genetic material that has the potential to store a lot of important information. Keywords: ancient man; DNA bacteria; dental calculus